Form and Function in a Legal System : a General Study - Summers, Robert S. (Mc Graw Hill, 2006)
This book addresses three major questions about law and legal systems: (1) What are the defining and organizing forms of legal institutions, legal rules, interpretive methodologies, and other legal phenomena? (2) How does frontal and systematic focus on these forms advance understanding of such phenomena? (3) What credit should the functions of forms have when such phenomena serve policy and related purposes, rule of law values, and fundamental political values such as democracy, liberty, and justice? The answers not only provide articulate conversancy with the subject but also reveal insights into the nature of law itself, as well as allied subjects.